Studi Metalografi Pengaruh Arus Dan Holding Time Pada Pengelasan Spot Welding Material Stainless Steel - Fahmi, Rinomo Muhammad, Muh Alfatih Hendrawan., ST., MT, Ir. Masyrukan., MT (2015)
In the spot welding process, namely process of joining two or more metal plates, there are many factors that must be considered. Welding current, electrical resistance, and the welding time is a major factor in the welding point. These factors may affect the quality of the weld. However, it is possible there are other factors that also affect the quality of the welding, one of which is the welding cycle including the holding time. This study aims to identify the chemical composition of the metal plate used in welding spot welding and also to observe the influence of currents and holding time physically with macro and micro observations photo area parent metal, HAZ, and weld metal regions. The material used in this study is stainless steel with a thickness of 0.8 mm. The parameters used in this study is the welding current 5 kA, 6 kA, and 7 kA, constant welding time of 0.3 seconds, with a variation of holding time of 1 second, 3 seconds, and 5 seconds. Test showed that the chemical composition of the material is stainless steel tipe316 included austenite phase. The observation shows that the current macro picture and holding time giving effect to the formation of the weld metal (nugget). The greater the flow and holding time is given, the resulting weld metal increases. On the micro photos observations on the test area of the parent metal, HAZ, and weld metal microstructure did not change, only the grain size and density differences, but these changes are not very significant.